Role of local heating in crystallization of amorphous alloys under ball milling: An experiment on Fe90Zr10 - Kwon, Y. S.; Kim, J. S.; Povstugar, I. V.; Yelsukov, E. P.; Choi, P. P. (AMERICAN PHYSICAL SOC, 2007)
Fe90Zr10 was chosen as a model system to elucidate the roles of mechanical deformation and local heating in the phenomenon of ball-milling-induced crystallization of amorphous alloys. The structural evolution of melt-spun amorphous Fe90Zr10 ribbons under different milling conditions and high-pressure torsion was investigated by means of x-ray diffraction, Mossbauer spectroscopy, and magnetic measurements. Despite a considerable difference in the local temperatures for high-energy and low-energy ball millings, cryomilling (under liquid nitrogen-cooling), and high-pressure torsion, amorphous Fe90Zr10 crystallizes into a supersaturated alpha-Fe(Zr) solid solution in all cases. Local heating occurring under high- and low-energy millings only plays a minor role and leads to a slight shift of the crystallization products towards equilibrium state. Mechanical deformation was established as the primary cause of crystallization of the amorphous Fe-Zr alloy under ball milling.
Keywords: FE-ZR SYSTEM; PHASE-TRANSFORMATIONS; MAGNETIC-PROPERTIES; NI-ZR; METALLIC GLASSES; ENERGY; SI; DEFORMATION; TEMPERATURE; MOSSBAUER